A Rechargeable Hydrogen Battery Based on Ru Catalysis. Issue 27 (6th May 2014) - Hsu, Shih‐Fan; Rommel, Susanne; Eversfield, Philipp; Muller, Keven; Klemm, Elias; Thiel, Werner R.; Plietker, Bernd
Abstract Apart from energy generation, the storage and liberation of energy are among the major problems in establishing a sustainable energy supply chain. Herein we report the development of a rechargeable H2 battery which is based on the principle of the Ru‐catalyzed hydrogenation of CO2 to formic acid (charging process) and the Ru‐catalyzed decomposition of formic acid to CO2 and H2 (discharging process). Both processes are driven by the same catalyst at elevated temperature either under pressure (charging process) or pressure‐free conditions (discharging process). Up to five charging–discharging cycles were performed without decrease of storage capacity. The resulting CO2/H2 mixture is free of CO and can be employed directly in fuel‐cell technology.